Processing of high sulphate and free lime calcareous coal fly ash for producing high volume blended cements and complying grade products employed in civil engineering - Altin Mele; Reinhard Trettin (Zaštita Materijala)
The present work outlines the results of a research attempt aimed at developing and evaluating the performance of processed fly ash. The raw fly ashes are very coarse, have variable chemical and mineralogical composition and contain higher than allowed amounts of sulphate and free lime. Furthermore these fly ashes contain enhanced levels of radionuclides (226Ra, 232Th, 40K), which originate from the parent coal mineral. The above listed properties prevent raw calcareous fly ashes to be employed as they are. Calcareous type lignite fly ash samples that were provided from various power plants were processed in ways which enable the highest possible and safe utilisation ratio of fly ash in cement and some civil engineering applications. The processing consisted mainly on blending and/or co-grinding whereby co-grinding was a combined grinding and hydrolisis in order to reduce the sulphate and free lime content of the blend. Provided an accurate and strict quality management system is available, calcareous fly ashes can easily and safely be employed at up to 50% ratio in blended cements that comply with the European standard requirement for cement. This processing way is an environmentally and economically sound alternative and probably one of the best strategies for the highest possible calcareous fly ash utilisation.